2018
DOI: 10.5114/aoms.2016.59894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and combined low frequency electromagnetic fields and simulated microgravity on gene expression of human mesenchymal stem cells during chondrogenesis

Abstract: IntroductionLow frequency electromagnetic fields (LF-EMF) and simulated microgravity (SMG) have been observed to affect chondrogenesis. A controlled bioreactor system was developed to apply LF-EMF and SMG singly or combined during chondrogenic differentiation of human mesenchymal stem cells (hMSCs) in 3D culture.Material and methodsAn external motor gear SMG bioreactor was combined with magnetic Helmholtz coils for EMF (5 mT; 15 Hz). Pellets of hMSCs (±TGF-β3) were cultured (P5) under SMG, LF-EMF, LF-EMF/SMG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Shorter SMG treatments appeared to inhibit osteogenesis[ 47 - 49 ] and promote endothelial cell differentiation[ 48 ], neuronal differentiation[ 44 , 48 ], and adipogenic differentiation[ 48 , 49 ]. However, extended SMG decreased the potential for chondrogenic differentiation in MSCs[ 50 ] and encouraged their differentiation toward osteogenesis[ 46 , 48 ]. Different SMG action times had different effects on the cytoskeleton and could even lead to the aforementioned changes through different signal transduction pathways.…”
Section: Physical Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter SMG treatments appeared to inhibit osteogenesis[ 47 - 49 ] and promote endothelial cell differentiation[ 48 ], neuronal differentiation[ 44 , 48 ], and adipogenic differentiation[ 48 , 49 ]. However, extended SMG decreased the potential for chondrogenic differentiation in MSCs[ 50 ] and encouraged their differentiation toward osteogenesis[ 46 , 48 ]. Different SMG action times had different effects on the cytoskeleton and could even lead to the aforementioned changes through different signal transduction pathways.…”
Section: Physical Stimulimentioning
confidence: 99%
“…In fact, the actual microenvironment in which cells were exposed was multifactorial. Therefore, some studies are now starting to consider the effect of compound factors[ 50 , 55 , 61 , 66 ] on the behavior of MSCs. Compound factors could have synergistic effects that increase the benefits for MSCs or counteract the drawbacks of a single factor.…”
Section: Physical Stimulimentioning
confidence: 99%
“…In this context, the exposure to the electromagnetic fields (EMFs) of cells grown in 3D cell systems is gaining a growing interest (mainly for tissue regeneration purposes), although the experimental data are still very limited [ 18 20 ]. A few reports characterized the response to the extremely low-frequency (ELF) magnetic field (MF) in both primary bovine chondrocytes and mesenchymal stem cells grown in 3D cultures to stimulate chondrogenesis and cartilage maturation [ 21 , 22 ], or in epidermal stem cells seeded in collagen sponge scaffolds for improving wound healing [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of magnetic fields influence biological activities [ 31 ], not only in osteoporosis [ 32 ] and orthodontics [ 33 ] but also with an active role in cartilage tissue engineering [ 34 ]. Related studies have provided evidence that moderate-intensity SMF can effectively promote chondrogenic differentiation of BMSCs [ 10 , 25 ]. Our earlier study tested different SMF strengths by exposing MCCs to 160, 280, or 360 mT and found that the proliferation and chondrogenesis-promoting effects of 280 mT SMF were the most pronounced [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The induction of BMSC chondrogenesis to repair articular cartilage defects has recently begun to be intensively studied [ 9 ]. Many studies focused on BMSCs from the femur and tibia [ 10 ]; however, few studies were interested in the mandibular BMSCs, which contribute to mandible development. At the 7 th week of the embryo [ 11 ], MBMSCs located at the base of the mandible gradually coagulated into a mass, and then the central cells of the mass differentiated into osteoblasts, finally forming the mandible by intramembrane osteogenesis.…”
Section: Introductionmentioning
confidence: 99%